CORE Teaching Model Based Mnemonic Technique Impact Students’ Mathematical Creative Thinking Ability and Metacognitive Awareness - Eka Widiyasari; Mujib Mujib; Suherman Suherman; Komarudin Komarudin; Bambang Sri Anggoro; Mardiyah Mardiyah (Department of Mathematics Education, Universitas Muhammadiyah Purwokerto, Indonesia, 2022)
The purpose of this study was to determine the effect of the Connecting, Organizing, Reflecting, and Extending (CORE) learning model with mnemonic techniques on students' creative thinking skills and metacognitive awareness. The research method was a quasi-experimental design. Data on creative thinking skills were collected using essay test instruments and metacognitive awareness using questionnaires. This research was conducted on the eighth-grade students of a secondary school in Tulang Baawang Lampung with a sample of 60 students taken by using the cluster random sampling technique. The data analysis technique was two-way ANOVA. Based on the test results, the first hypothesis is shown F(2) = 12.92, p < .05, the CORE learning model affects mnemonic techniques on students' creative thinking abilities. The second hypothesis shows F(2) = 19.97, p < .05, the high, medium, and low metacognitive awareness categories affect students' creative thinking abilities. The third hypothesis shows that F(4) = 1.65, p < .05, there is no interaction between the CORE learning model and mnemonic techniques with metacognitive awareness of students' creative thinking abilities. The impact of this research is the model can be a solution for mathematics teaching and learning.